Plugging material as well as preparation method and application thereof
By using PETA modified bisphenol A epoxy resin and m-phenylenediamine/methacrylic acid and other raw materials, the crosslinking structure enhances high temperature and high salt resistance, and solves the polymer in the prior art The shortcomings of the microsphere sealing system in high temperature, high salt and heterogeneous reservoirs have achieved the goal of efficient sealing and simplifying the process.
Patent Information
- Application Number
- CN202411436578.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-17
AI Technical Summary
The existing polymer microsphere sealing system is difficult to effectively seal in high-temperature, high-salt and heterogeneous reservoirs, and the preparation process is complex and cannot meet the actual on-site needs.
Using PETA modified bisphenol A type epoxy resin, m-phenylenediamine/methacrylic acid addition products and nano-silica dispersions, high temperature and high salt resistant microsphere sealing materials are prepared through emulsification and curing process. PETA molecules are embedded in the epoxy resin chain to form a crosslinked structure, enhance the sealing performance, and control the phase change time by adjusting the raw material ratio.
It significantly improves the high temperature and high salt resistance and sealing efficiency of the sealing material, simplifies the preparation process, adapts to complex reservoir conditions, improves the injectability and effective content of the glue-forming liquid, and is suitable for on-site applications.
Smart Images

Figure CN119320626A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oilfield chemistry, and in particular to a plugging material and a preparation method and application thereof. Background Art
[0002] Low permeability and heterogeneity have become the main characteristics of oil reservoir exploitation in my country. In the secondary oil recovery process, these characteristics usually lead to problems such as low reserve activation rate and short water breakthrough period, which seriously reduce the development efficiency. Oil well water plugging technology is the most direct and effective means to solve these problems. Among them, chemical water plugging is widely used because of its strong controllability and wide adaptability. However, when dealing with harsh conditions, the current conventional chemical water plugging system often cannot meet the needs.
[0003] The polymer microsphere system is an emerging water plugging technology. According to the injection method, it can be divided into two categories: pre-synthesized microspheres before injection and self-generated microspheres in the reservoir after injection. Current research mainly focuses on pre-synthesized microspheres before injection. Its plugging mechanism is to select polymer microspheres with particle sizes that match the pore throats of the formation, which are carried to the deep formation by the injection fluid. The microspheres absorb water and swell during the injection process, thereby plugging the high permeability layer. The self-generated microspheres in the reservoir after injection are to inject the gel-forming liquid directly into the formation, and gradually solidify into hard microspheres in the pore throats by the shear force during the flow process, and achieve the water plugging effect through the physical method of large particles blocking the seams and small particles bridging. Due to its unique plugging mechanism, this technology is considered to be an effective means of plugging micropore throats (20-50μm) in low permeability reservoirs. However, there are still many problems when existing research on polymer microsphere systems is applied on site. The preparation and application process of pre-synthesized microspheres are complicated and cannot withstand high-pressure plugging. The gelling liquid composition of self-generated microspheres in the reservoir is complex and has poor stability, and the phase change time is short, making it difficult to accurately reach the target layer. The microsphere production after the phase change cannot be controlled, which can easily cause damage to the reservoir, and the plugging mechanism is single.
[0004] The patent document with publication number CN111234792A discloses a polymer microsphere water plugging and profile control agent. The system successfully prepared polymer microspheres by dispersion polymerization. The initial particle size ranged from submicron to micron, and exhibited good expansion properties. Within the first 7 days, the microspheres expanded rapidly, with a final expansion rate of up to 120 times and could stably exist for up to 6 months at 90°C and a mineralization of 20,000 mg / L. Under experimental conditions, the system demonstrated excellent water plugging and profile control performance, but its application process is still complicated. According to patent disclosure information, the effective content of the system is as high as 26.3%, indicating that the preparation cost of the system is high and is not suitable for direct field application. The patent document with publication number CN113025293A discloses an epoxy resin self-generated particle profile adjustment system and its application method. The system mixes epoxy resin, emulsifier and dispersant into tap water at a temperature of 40-65°C and a stirring speed of 600r / min to prepare a stable O / W type emulsion. When injected, the curing agent is mixed in a corresponding proportion at a high stirring speed of 1000r / min. The prepared gelling liquid can gradually begin to solidify after the formation temperature reaches above 70°C and is completely solidified within 12 hours. According to the different shear forces provided, the particle size distribution of the microspheres is between 60 and 1000μm. Through subsequent double-tube experiments, it is verified that the system can still effectively block the high permeability layer when the permeability range is 10.4. However, the original configuration process did not consider the influence of mineralization on the stability of the gelling liquid. The stirring speed of 1000r / min required for injection puts high requirements on the on-site construction conditions, and it is impossible to control the curing time in the layer after the system is injected.
[0005] It can be seen that although the above two systems have made some progress under ideal experimental conditions, they have not fully taken into account the actual conditions of the reservoir, such as high temperature, high salinity, low permeability and heterogeneity. Therefore, it is necessary to develop a new polymer microsphere plugging system that is resistant to high temperature and high salinity, has strong plugging performance and is suitable for microchannel environments based on existing research. Summary of the invention
[0006] The purpose of the present invention is to overcome the above technical deficiencies, provide a plugging material and a preparation method and application thereof, and solve the technical problem that the polymer microsphere plugging system in the prior art is difficult to meet the requirements of high temperature and high salt resistance and strong plugging performance.
[0007] In order to achieve the above technical purpose, the technical solution of the present invention provides a plugging material, which is made from the following raw materials in parts by mass, wherein the raw materials include: 1 to 3.6 parts of PETA modified bisphenol A epoxy resin, 1.5 to 2.4 parts of meta-phenylenediamine / methacrylic acid addition product, 0.12 to 0.17 parts of nano-silicon dioxide dispersion, and the remainder is water, and the sum of the above raw materials is 100 parts.
[0008] In any embodiment, the raw material further comprises 0 to 0.14 parts of dibenzoyl peroxide.
[0009] In any embodiment, the PETA-modified bisphenol A epoxy resin is prepared by the following steps:
[0010] Bisphenol A epoxy resin, PETA (i.e. pentaerythritol triacrylate) and a first catalyst are mixed, and stirred for reaction at 40-50° C. to obtain the PETA-modified bisphenol A epoxy resin.
[0011] In any embodiment, the mass ratio of the bisphenol A epoxy resin to the PETA is 1:(0.25-0.3); and / or, the first catalyst is triphenylphosphine, and the amount of the first catalyst added is 0.1%-2% of the total mass of the bisphenol A epoxy resin and the PETA.
[0012] In any embodiment, the PETA-modified bisphenol A epoxy resin is obtained by reacting at 40-50° C. under nitrogen protection at a stirring speed of 100-200 r / min for 2-4 hours.
[0013] In any embodiment, the m-phenylenediamine / methacrylic acid addition product is prepared by the following steps:
[0014] The m-phenylenediamine, methacrylic acid and the second catalyst are mixed, and stirred to react at 25° C. to 60° C. and pH 8 to 9 for 4 h to 6 h to obtain the m-phenylenediamine / methacrylic acid addition product.
[0015] In any embodiment, the mass ratio of the m-phenylenediamine to the methacrylic acid is 1:(0.8-1.6); and / or the second catalyst is potassium carbonate, and the added amount of the second catalyst is 1%-5% of the total mass of the m-phenylenediamine and the methacrylic acid.
[0016] In addition, the present invention also provides a method for preparing the above-mentioned plugging material, comprising the following steps:
[0017] Step S1, preparation of oil phase and water phase: PETA modified bisphenol A epoxy resin and m-phenylenediamine / methacrylic acid addition product are mixed to form an oil phase mixture; nano-silicon dioxide dispersion is mixed with water to prepare a water phase mixture;
[0018] Step S2, emulsification process: pouring the water phase mixture into the continuously stirred oil phase mixture, and continuing to stir to form a gelling liquid;
[0019] Step S3, curing process: mixing the gelling liquid with dibenzoyl peroxide, stirring and reacting at 50° C. to 120° C. to obtain the plugging material.
[0020] In any embodiment, in step S2, the stirring is continued for 20-30 minutes; and / or, in step S3, the stirring reaction is carried out at 50° C. to 120° C. for 4-12 hours.
[0021] In addition, the present invention also proposes an application of the plugging material or the plugging material prepared by the preparation method in water plugging of oil reservoirs.
[0022] Compared with the prior art, the beneficial effects of the present invention include: the plugging material proposed in the present invention is made of the following raw materials in parts by mass, the raw materials include: 1 to 3.6 parts of PETA modified bisphenol A epoxy resin, 1.5 to 2.4 parts of m-phenylenediamine / methacrylic acid addition product, 0.12 to 0.17 parts of nano-silicon dioxide dispersion, the remainder is water, and the sum of the parts by mass of the above raw materials is 100 parts; PETA modified bisphenol A epoxy resin, PETA molecules are embedded in the bisphenol A epoxy resin chain, so that the surface of the microspheres has potential active cross-linking sites. Under appropriate activation conditions, cross-linking reactions will occur between the sites on the surface of adjacent microspheres, thereby aggregating to form a multi-microsphere cross-linked structure, achieving a synergistic effect between physics and chemistry, significantly enhancing the plugging ability of the system after phase change, and further under the synergistic effect of other raw materials, the plugging material obtained is resistant to high temperature and high salt and has strong plugging performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Schematic diagram of the structure of the PETA-modified bisphenol A epoxy resin (n=1) of the present invention.
[0024] Figure 2 The diagram is a schematic diagram of the molecular structure of two different monomer forms of the synthetic emulsifying curing agent of the present invention.
[0025] Figure 3 The phase transition time and microsphere morphology of the system under different mineralization degrees in experimental group 1.
[0026] Figure 4 The cross-linked structure morphology is formed between the microspheres prepared in Examples 1-5 of Experimental Group 1.
[0027] Figure 5 The distribution pattern of the microspheres prepared in Example 3 of Experimental Group 2 in porous media with different permeabilities.
[0028] Figure 6 The mass retention rate of the microspheres prepared in Example 2 and Example 4 of Test Group 3 after aging.
[0029] Figure 7 This is the thermogravimetric analysis diagram of the microspheres prepared in Example 2 and Example 4 of Experimental Group 3. DETAILED DESCRIPTION
[0030] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0031] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0032] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0033] This specific embodiment provides a plugging material, which is made from the following raw materials in parts by mass, including: 1 part to 3.6 parts of PETA modified bisphenol A epoxy resin, 1.5 parts to 2.4 parts of meta-phenylenediamine / methacrylic acid addition product, 0.12 parts to 0.17 parts of nano-silicon dioxide dispersion, and the remainder is water. The sum of the parts by mass of the above raw materials is 100 parts.
[0034] In some embodiments, 0 to 0.14 parts of dibenzoyl peroxide are also included. When dibenzoyl peroxide is added, the introduced surface self-crosslinking groups can also be activated by dibenzoyl peroxide at low temperatures, thereby achieving self-crosslinking of microspheres at low temperatures.
[0035] In some embodiments, the PETA-modified bisphenol A epoxy resin is prepared by the following steps:
[0036] Bisphenol A epoxy resin, PETA and the first catalyst are mixed, and reacted at 40°C to 50°C under nitrogen protection at a stirring speed of 100r / min to 200r / min for 2h to 4h to obtain the PETA-modified bisphenol A epoxy resin; the mass ratio of the bisphenol A epoxy resin to the PETA is 1:(0.25 to 0.3); the first catalyst is triphenylphosphine, and the amount of the first catalyst added is 0.1% to 2% of the total mass of the bisphenol A epoxy resin and the PETA. In the present invention, PETA is used to modify the bisphenol A epoxy resin, and the self-crosslinking between adjacent microspheres is successfully achieved, which effectively improves the sealing performance of the material. Furthermore, the PETA molecule contains three unsaturated double bonds and can copolymerize with the epoxy resin monomer. By precisely controlling the amount of PETA, the type of catalyst, and the temperature and time of the reaction, some of the unsaturated double bonds can be involved in the copolymerization, and the PETA molecules can be embedded in the epoxy resin chain. The molecular structure after modification is shown as follows. Figure 1 As shown. The unsaturated double bonds that do not participate in the copolymerization are located on the surface of the particles. During the curing process, some of them participate in the reaction, and some are reserved for automatic crosslinking at high temperatures (≥100°C). Under medium and low temperature conditions (50-100°C), an activator is needed to promote the crosslinking reaction.
[0037] In some embodiments, the m-phenylenediamine / methacrylic acid addition product is prepared by the following steps:
[0038] Mix m-phenylenediamine, methacrylic acid and a second catalyst, and react by stirring at 25° C. to 60° C. to obtain the m-phenylenediamine / methacrylic acid addition product; the mass ratio of the m-phenylenediamine to the methacrylic acid is 1:(0.8 to 1.6); the second catalyst is potassium carbonate, and the addition amount of the second catalyst is 1% to 5% of the total mass of the m-phenylenediamine and the methacrylic acid.
[0039] In the present invention, by adjusting the ratio of m-phenylenediamine and methacrylic acid during synthesis, and the amount of PETA-modified bisphenol A epoxy resin, the phase transition time of the system can be effectively controlled. Furthermore, during the reaction, mono-addition products and di-addition products will be formed according to the amount of methacrylic acid used. The more sufficient the addition, the more secondary amines there are. The molecular structures of the two product monomers are as follows: Figure 2 As shown, Figure 2 (a) is a monoaddition product, Figure 2 (b) is a double addition product. The addition product of the two is an aromatic diamine. The reaction formula of the polyamine during the curing process with epoxy resin is as follows:
[0040]
[0041] It should be noted that R1 and R2 are the segments after the reactive groups are removed. The above reaction formula is only used to represent the process of the amine group of the polyamine curing epoxy resin; because the curing process only involves the reaction between the amine group and the epoxy group, it does not need to be specifically shown.
[0042] First, the active hydrogen of the primary amine reacts with the epoxy group to generate a secondary amine, which then continues to react to generate a tertiary amine, and finally forms a cross-linked network structure. The generated tertiary amine has a catalytic effect on the curing reaction. Aromatic polyamines are affected by the steric hindrance of their own aromatic rings, and the two-step reaction time is relatively long. Therefore, the more secondary amines there are in the addition product, the shorter the time it takes to form a tertiary amine, and the corresponding curing phase transition time is shortened. Conversely, the less secondary amines there are, the longer the curing phase transition time is. Adjusting the dosage of the main agent will directly affect the content of the epoxy group, and thus the phase transition time can also be adjusted within a certain range.
[0043] In the present invention, PETA modified bisphenol A type epoxy resin is the main agent, metaphenylenediamine / methacrylic acid addition product is the emulsifying curing agent, dibenzoyl peroxide is the activator, nano silicon dioxide dispersion is the dispersant, and water is the system dispersed phase. The aromatic ring in the skeleton of PETA-modified bisphenol A epoxy resin provides toughness and heat resistance, the ether bond imparts chemical resistance, the epoxy group imparts reactivity, and the unsaturated double bonds that do not participate in copolymerization are retained on the modified side chains, providing cross-linking sites on the surface of the microspheres, thus providing an excellent reaction basis; the metaphenylenediamine / methacrylic acid addition product has a hydrophilic carboxyl group and a lipophilic aromatic skeleton, and has an amphiphilic structure that makes it an ideal emulsifier. It also contains an amino group that can react with the epoxy group, playing a role in curing the epoxy resin; dibenzoyl peroxide can decompose at a lower temperature to produce free radicals, thereby initiating free radical polymerization of the acrylate groups in the PETA molecular chain; the nano-silica dispersion can form mechanical isolation on the surface of the uncured particles, effectively preventing the uncured particles from aggregating prematurely, and further increasing the compressive resistance of the hard microspheres after the phase change.
[0044] This specific embodiment also proposes a method for preparing the above-mentioned plugging material, comprising the following steps:
[0045] Step S1, preparation of oil phase and water phase: PETA modified bisphenol A epoxy resin and m-phenylenediamine / methacrylic acid addition product are mixed to form an oil phase mixture; nano-silicon dioxide dispersion is mixed with water to prepare a water phase mixture;
[0046] Step S2, emulsification process: pour the water phase mixture into the continuously stirred oil phase mixture, and continue stirring for 20 minutes to 30 minutes to form a gel solution;
[0047] Step S3, curing process: the gelling liquid is transferred to be mixed with dibenzoyl peroxide, and stirred at 50° C. to 120° C. for 4 h to 12 h to obtain the plugging material.
[0048] In addition, this specific embodiment also proposes an application of the above-mentioned plugging material or the plugging material prepared by the above-mentioned preparation method in water plugging of oil reservoirs.
[0049] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0050] In the present invention, reference is made to “some embodiments”, “this embodiment”, examples, etc., which describe a subset of all possible embodiments, but it can be understood that “some embodiments” may be the same subset or different subsets of all possible embodiments and may be combined with each other without conflict.
[0051] If similar descriptions of "first / second" appear in the application documents, the following instructions are added. In the following description, the terms "first\second\third" involved are merely used to distinguish similar objects and do not represent a specific ordering of the objects. It is understandable that "first\second\third" can be interchanged in a specific order or sequence where permitted, so that the embodiments described herein can be implemented in an order other than that illustrated or described herein.
[0052] In this embodiment, the term "and / or" is merely a description of the association relationship between associated objects, indicating that three relationships may exist. For example, object A and / or object B may represent three situations: object A exists alone, object A and object B exist at the same time, and object B exists alone.
[0053] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0054] In the following examples or comparative examples, the water is simulated formation water with a mineralization of 30,000 mg / L.
[0055] Nano-silicon dioxide dispersion: Wuhan Jiyesheng Chemical Co., Ltd., effective content is 30%.
[0056] The bisphenol A epoxy resin monomer has a viscosity of 2500 mPa·s at 40° C. and an epoxy value of 0.48 to 0.54.
[0057] In the following embodiments or comparative examples, the PETA-modified bisphenol A epoxy resin is prepared by the following steps: the mass ratio of bisphenol A epoxy resin to PETA is 1:0.25; the catalyst is triphenylphosphine, and the amount thereof is 0.5% of the total mass of the reactants; the experimental temperature is controlled at 40° C., and the reaction is carried out at 200 r / min for 3 h under nitrogen protection.
[0058] In the following examples, the m-phenylenediamine / methacrylic acid addition product is prepared by the following steps: m-phenylenediamine and methacrylic acid are mixed in a mass ratio of 1:0.8, and potassium carbonate accounting for 2% of the total mass of m-phenylenediamine and methacrylic acid is added, and stirred at a temperature of 45° C. for 4 hours.
[0059] Example 1
[0060] This embodiment proposes a microchannel controllable self-phase change microsphere plugging system (i.e., plugging material), which is prepared from the following raw materials in parts by mass, wherein the raw materials include: 1 part of PETA-modified bisphenol A epoxy resin, 1.5 parts of m-phenylenediamine / methacrylic acid addition product, 0.14 parts of dibenzoyl peroxide, 0.17 parts of nano-silicon dioxide dispersion, and the remainder is water, and the sum of the parts by mass of the above raw materials is 100 parts.
[0061] The preparation method of the microchannel controllable self-phase change microsphere plugging system is as follows, according to the above raw material ratio:
[0062] Step S1, preparation of the oil phase and water phase of the system: at room temperature, 1 part of PETA modified bisphenol A epoxy resin and 1.5 parts of m-phenylenediamine / methacrylic acid addition product were mixed, and stirred at a speed of 300 r / min for 15 min to form an oil phase mixture; at the same time, 0.17 parts of nano-silicon dioxide dispersion were mixed with 97.19 parts of water, and stirred at a speed of 300 r / min for 10 min to prepare a water phase mixture;
[0063] Step S2, emulsification process: slowly pour the water phase into the continuously stirred oil phase, maintain the stirring speed at 300 r / min, and continue for 25 minutes to form a stable gelling solution;
[0064] Step S3, curing process: transfer the gelling solution to a three-necked flask and add 0.14 parts of dibenzoyl peroxide, control the water bath temperature at 50° C., and continue stirring at a speed of 300 r / min until the system is completely transformed into hard microspheres.
[0065] Example 2
[0066] This embodiment proposes a microchannel controllable self-phase change microsphere plugging system (i.e., plugging material), which is prepared from the following raw materials in parts by mass, wherein the raw materials include: 1 part of PETA-modified bisphenol A epoxy resin, 1.5 parts of m-phenylenediamine / methacrylic acid addition product, 0.08 parts of dibenzoyl peroxide, 0.17 parts of nano-silicon dioxide dispersion, and the remainder is water, and the sum of the parts by mass of the above raw materials is 100 parts.
[0067] The preparation method of the microchannel controllable self-phase change microsphere plugging system is as follows, according to the above raw material ratio:
[0068] Step S1, preparation of the oil phase and water phase of the system: at room temperature, PETA modified bisphenol A epoxy resin and m-phenylenediamine / methacrylic acid addition product are mixed and stirred at a speed of 300 r / min for 15 min to form an oil phase mixture; at the same time, the nano-silicon dioxide dispersion is mixed with water and stirred at a speed of 300 r / min for 10 min to prepare a water phase mixture;
[0069] Step S2, emulsification process: slowly pour the water phase into the continuously stirred oil phase, maintain the stirring speed at 300 r / min, and continue for 25 minutes to form a stable gelling solution;
[0070] Step S3, curing process: the gelling solution was transferred to a three-necked flask and dibenzoyl peroxide was added, the water bath temperature was controlled at 70° C., and stirring was continued at a speed of 300 r / min until the system was completely transformed into hard microspheres.
[0071] Example 3
[0072] This embodiment proposes a microchannel controllable self-phase change microsphere plugging system (i.e., plugging material), which is prepared from the following raw materials in parts by mass, wherein the raw materials include: 1.8 parts of PETA-modified bisphenol A epoxy resin, 1.8 parts of m-phenylenediamine / methacrylic acid addition product, 0.03 parts of dibenzoyl peroxide, 0.12 parts of nano-silicon dioxide dispersion, and the remainder is water, and the sum of the parts by mass of the above raw materials is 100 parts.
[0073] The preparation method of the microchannel controllable self-phase change microsphere plugging system of this embodiment is as follows, according to the above raw material ratio:
[0074] Step S1, preparation of the oil phase and water phase of the system: at room temperature, PETA modified bisphenol A epoxy resin and m-phenylenediamine / methacrylic acid addition product were mixed and stirred at a speed of 300 r / min for 15 min to form an oil phase mixture; at the same time, the nano-silicon dioxide dispersion was mixed with 97.19 parts of water and stirred at a speed of 300 r / min for 10 min to prepare a water phase mixture;
[0075] Step S2, emulsification process: slowly pour the water phase into the continuously stirred oil phase, maintain the stirring speed at 300 r / min, and continue for 25 minutes to form a stable gelling solution;
[0076] Step S3, curing process: transfer the gelling solution to a three-necked flask and add dibenzoyl peroxide, control the water bath temperature at 90° C., and continue stirring at a speed of 300 r / min until the system is completely transformed into hard microspheres.
[0077] Example 4
[0078] This embodiment proposes a microchannel controllable self-phase change microsphere plugging system (i.e., plugging material), which is prepared from the following raw materials in parts by mass, wherein the raw materials include: 3.6 parts of PETA-modified bisphenol A epoxy resin, 2 parts of m-phenylenediamine / methacrylic acid addition product, 0 parts of dibenzoyl peroxide, 0.16 parts of nano-silicon dioxide dispersion, and the remainder is water, and the sum of the parts by mass of the above raw materials is 100 parts.
[0079] The preparation method of the microchannel controllable self-phase change microsphere plugging system is as follows, according to the above raw material ratio:
[0080] Step S1, preparation of the oil phase and water phase of the system: at room temperature, PETA modified bisphenol A epoxy resin and m-phenylenediamine / methacrylic acid addition product are mixed and stirred at a speed of 300 r / min for 15 min to form an oil phase mixture; at the same time, the nano-silicon dioxide dispersion is mixed with water and stirred at a speed of 300 r / min for 10 min to prepare a water phase mixture;
[0081] Step S2, emulsification process: slowly pour the water phase into the continuously stirred oil phase, maintain the stirring speed at 300 r / min, and continue for 25 minutes to form a stable gelling solution;
[0082] Step S3, curing process: the gelling solution was transferred to a three-necked flask, the oil bath temperature was controlled at 110° C., and stirring was continued at a speed of 300 r / min until the system was completely transformed into hard microspheres.
[0083] Example 5
[0084] This embodiment proposes a microchannel controllable self-phase change microsphere plugging system (i.e., plugging material), which is prepared from the following raw materials in parts by mass, wherein the raw materials include: 3.6 parts of PETA-modified bisphenol A epoxy resin, 2.4 parts of m-phenylenediamine / methacrylic acid addition product, 0 parts of dibenzoyl peroxide, 0.16 parts of nano-silicon dioxide dispersion, and the remainder is water, and the sum of the parts by mass of the above raw materials is 100 parts.
[0085] The preparation method of the microchannel controllable self-phase change microsphere plugging system is as follows, according to the above raw material ratio:
[0086] Step S1, preparation of the oil phase and water phase of the system: at room temperature, PETA modified bisphenol A epoxy resin and m-phenylenediamine / methacrylic acid addition product are mixed and stirred at a speed of 300 r / min for 15 min to form an oil phase mixture; at the same time, the nano-silicon dioxide dispersion is mixed with water and stirred at a speed of 300 r / min for 10 min to prepare a water phase mixture;
[0087] Step S2, emulsification process: slowly pour the water phase into the continuously stirred oil phase, maintain the stirring speed at 300 r / min, and continue for 25 minutes to form a stable gelling solution;
[0088] Step S3, curing process: the gelling solution was transferred to a three-necked flask, the oil bath temperature was controlled at 120° C., and stirring was continued at a speed of 300 r / min until the system was completely transformed into hard microspheres.
[0089] Example 6
[0090] The plugging material of this comparative example is different from that of Example 3 only in that in the preparation of the meta-phenylenediamine / methacrylic acid addition product, the mass ratio of meta-phenylenediamine and methacrylic acid addition is 1:1, and other raw materials and preparation methods are the same as those of Example 3.
[0091] Example 7
[0092] The plugging material of this comparative example is different from that of Example 3 only in that in the preparation of the meta-phenylenediamine / methacrylic acid addition product, the mass ratio of meta-phenylenediamine and methacrylic acid addition is 1:1.2, and the other raw materials and preparation method are the same as those of Example 3.
[0093] Example 8
[0094] The plugging material of this comparative example is different from that of Example 3 only in that in the preparation of the meta-phenylenediamine / methacrylic acid addition product, the mass ratio of meta-phenylenediamine and methacrylic acid addition is 1:1.4, and the other raw materials and preparation method are the same as those of Example 3.
[0095] Example 9
[0096] The plugging material of this comparative example is different from that of Example 3 only in that in the preparation of the meta-phenylenediamine / methacrylic acid addition product, the mass ratio of meta-phenylenediamine and methacrylic acid addition is 1:1.6, and the other raw materials and preparation method are the same as those of Example 3.
[0097] Example 10
[0098] The only difference between the plugging material of this comparative example and Example 3 is that in the preparation of the meta-phenylenediamine / methacrylic acid addition product, the mass ratio of meta-phenylenediamine and methacrylic acid addition is 1:0.8, the addition amount of PETA modified bisphenol A type epoxy resin is 2.4 parts, and the other raw materials and preparation methods are the same as those in Example 3.
[0099] Comparative Example 1
[0100] This embodiment proposes a microchannel controllable self-phase change microsphere plugging system (i.e., plugging material), which is prepared from the following raw materials in parts by mass, comprising: 1.8 parts of bisphenol A epoxy resin, 1.8 parts of m-phenylenediamine / methacrylic acid addition product, 0.12 parts of nano-silicon dioxide dispersion, 0.03 parts of dibenzoyl peroxide, and the remainder is water, and the sum of the parts by mass of the above raw materials is 100 parts.
[0101] The preparation method of the microchannel controllable self-phase change microsphere plugging system of this embodiment is as follows, according to the above raw material ratio:
[0102] Step S1, preparation of the oil phase and water phase of the system: at room temperature, bisphenol A epoxy resin and m-phenylenediamine / methacrylic acid addition product are mixed, and stirred at a speed of 300 r / min for 15 min to form an oil phase mixture; at the same time, the nano-silicon dioxide dispersion is mixed with water, and stirred at a speed of 300 r / min for 10 min to prepare a water phase mixture;
[0103] Step S2, emulsification process: slowly pour the water phase into the continuously stirred oil phase, maintain the stirring speed at 300 r / min, and continue for 25 minutes to form a stable gelling solution;
[0104] Step S3, curing process: transfer the gelling solution to a three-necked flask and add dibenzoyl peroxide, control the water bath temperature at 90° C., and continue stirring at a speed of 300 r / min until the system is completely transformed into hard microspheres.
[0105] Experimental Group 1
[0106] The above Examples 1-5 were respectively prepared into gel solution with simulated formation water of mineralization degree 10000mg / L, 20000mg / L, 30000mg / L and 50000mg / L, and the phase transition time of the system and the morphology of the microspheres after the phase transition were observed. Figure 3 and Figure 4 shown.
[0107] See also Figure 3 and Figure 4 ,pass Figure 3It can be seen that as the mineralization of the simulated formation water increases, the dispersion of most of the microspheres prepared at the same temperature becomes better, the sphericity increases, and the particle size range decreases accordingly. This shows that the microsphere plugging system of the present invention can effectively adapt to high-salinity environments. Figure 4 It can be seen that a small number of adjacent microspheres can form a cross-linked structure.
[0108] Experimental Group 2
[0109] The above Example 3 was injected into sand-filled pipes with permeabilities of 5523.6mD, 3281.5mD, and 1125.8mD, and after being fully matured at 90°C, a subsequent water flooding experiment was performed to determine the plugging rate. After the water flooding was completed, the distribution of microspheres in porous media with different permeabilities was observed, as shown in Table 1 and Figure 5 .
[0110] Please refer to Table 1 and Figure 5 It can be seen from Table 1 that the plugging rate of the system reached more than 90% under the premise of an effective content of 3.75%, and the particle size of the microspheres can change adaptively with the change of the permeability of the sand filling pipe; Figure 5 It can be seen that the system forms fewer particles at the inlet end of the sand filling tube, which are mainly concentrated in the middle and rear ends. Some microspheres are cross-linked to form a three-dimensional structure, which effectively blocks the pores.
[0111] Table 1 Water flooding experimental results of microchannel controllable self-phase change microsphere plugging system at different permeabilities
[0112]
[0113] Experimental Group 3
[0114] The microspheres prepared in Example 2 and Example 4 were subjected to thermal stability evaluation and thermogravimetric analysis. Figure 6 and Figure 7 .
[0115] See also Figure 6 and Figure 7 ,pass Figure 6 It can be seen that the mass retention rate of the microspheres at their corresponding temperatures after aging for 100 days is greater than 99%. Figure 7 It can be seen that the temperature at which the microspheres lose 5% of their weight is greater than 250° C., and the temperature at which they lose 10% of their weight is greater than 300° C. This indicates that the microspheres have excellent thermal stability and aging resistance after the phase transition of the system, and can meet the needs of long-term high-temperature plugging in the reservoir.
[0116] Experimental Group 4
[0117] By comparing and evaluating Example 3 with Examples 6-10, the effects of the amount of PETA-modified bisphenol A epoxy resin and the degree of addition of m-phenylenediamine / methacrylic acid on the phase change time of the system were obtained, as shown in Table 2 below.
[0118] Please refer to Table 2. It can be seen from Table 2 that the data shown in the table show that by adjusting the ratio of the reactants of m-phenylenediamine and methacrylic acid, and adjusting the addition amount of PETA-modified bisphenol A epoxy resin, the phase transition time of the system can be effectively controlled. This shows that the water plugging system proposed in the present invention can achieve precise plugging effect.
[0119] Table 2 Comparison of system raw material dosage and phase transition time
[0120]
[0121] Experimental Group 5
[0122] The modified system (i.e., Example 3) and the unmodified system (i.e., Comparative Example 1) prepared in Example 3 and Comparative Example 1 were respectively injected into two groups of sand-filled pipes with similar permeabilities. After being fully matured at 90° C., a long-term subsequent water flooding test was carried out to obtain the scour resistance of different systems.
[0123] Please refer to Table 3. It can be seen from Table 3 that the data shown in the table show that the plugging rate retention rate of the modified system after 20PV water flooding is much higher than that of the unmodified system. This shows that the three-dimensional structure formed by cross-linking of microspheres prepared in the modified system can effectively enhance the mechanical properties during plugging and improve the scouring resistance of the system.
[0124] Table 3 Changes in system plugging rate after long-term water flooding
[0125]
[0126] Other beneficial effects:
[0127] 1) Microchannel controllable self-phase change microsphere plugging system PETA modified bisphenol A epoxy resin was developed. During the synthesis process, PETA molecules were embedded into the bisphenol A epoxy resin chain, so that the surface of the microspheres has potential active cross-linking sites. Under appropriate activation conditions, cross-linking reactions will occur between sites on the surface of adjacent microspheres, thereby aggregating to form a multi-microsphere cross-linked structure, achieving a synergistic effect between physics and chemistry, and significantly enhancing the plugging ability of the system after phase change.
[0128] 2) The microchannel controllable self-phase change microsphere plugging system simplifies the existing system composition and significantly enhances the temperature and salt resistance of the gelling liquid by introducing rigid groups. At the same time, the ratio of the synthetic raw materials of the emulsified curing agent can be adjusted according to the plugging position to change the curing time of the system, so that the phase change time can be adjusted between 4 and 12 hours, achieving the purpose of precise plugging for specific well sections.
[0129] 3) The effective content of the microchannel controllable self-phase change microsphere plugging system is as high as 6.16%, and the viscosity of the gelling liquid in the temperature range of 50℃~120℃ is as low as 3~7mPa·s, which greatly improves the injectability of the gelling liquid. The preparation and application process are simple, which meets the requirements of actual field application.
[0130] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A plugging material, characterized in that: The invention is prepared from the following raw materials in parts by weight: 1 to 3.6 parts of PETA modified bisphenol A epoxy resin, 1.5 to 2.4 parts of m-phenylenediamine / methacrylic acid addition product, 0.12 to 0.17 parts of nano silicon dioxide dispersion, and the balance is water, and the sum of the parts by weight of the above raw materials is 100 parts.
2. The plugging material according to claim 1, characterized in that: The raw materials also include 0 to 0.14 parts of dibenzoyl peroxide.
3. The plugging material according to claim 1, characterized in that: The PETA modified bisphenol A type epoxy resin is prepared by the following steps: Bisphenol A epoxy resin, PETA and a first catalyst are mixed, and stirred for reaction at 40-50° C. to obtain the PETA-modified bisphenol A epoxy resin.
4. The plugging material according to claim 3, characterized in that: The mass ratio of the bisphenol A epoxy resin to the PETA is 1:(0.25-0.3); and / or, the first catalyst is triphenylphosphine, and the addition amount of the first catalyst is 0.1%-2% of the total mass of the bisphenol A epoxy resin and the PETA.
5. The plugging material according to claim 3, characterized in that: The PETA-modified bisphenol A epoxy resin is obtained by reacting at 40° C. to 50° C. under nitrogen protection at a stirring speed of 100 r / min to 200 r / min for 2 h to 4 h.
6. The plugging material according to claim 1, characterized in that: The m-phenylenediamine / methacrylic acid addition product is prepared by the following steps: The m-phenylenediamine, methacrylic acid and the second catalyst are mixed, and stirred for reaction at 25° C. to 60° C. to obtain the m-phenylenediamine / methacrylic acid addition product.
7. The plugging material according to claim 6, characterized in that: The mass ratio of the m-phenylenediamine to the methacrylic acid is 1:(0.8-1.6); and / or the second catalyst is potassium carbonate, and the added amount of the second catalyst is 1-5% of the total mass of the m-phenylenediamine and the methacrylic acid.
8. A method for preparing the plugging material according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step S1, preparation of oil phase and water phase: PETA modified bisphenol A epoxy resin and m-phenylenediamine / methacrylic acid addition product are mixed to form an oil phase mixture; nano-silicon dioxide dispersion is mixed with water to prepare a water phase mixture; Step S2, emulsification process: pouring the water phase mixture into the continuously stirred oil phase mixture, and continuing to stir to form a gelling liquid; Step S3, curing process: mixing the gelling liquid with dibenzoyl peroxide, stirring and reacting at 50° C. to 120° C. to obtain the plugging material.
9. The method for preparing the plugging material according to claim 8, characterized in that: In step S2, the stirring time is continued for 20 minutes to 30 minutes; and / or, in step S3, the stirring reaction time at 50° C. to 120° C. is 4 hours to 12 hours.
10. Use of the plugging material according to any one of claims 1 to 7 or the plugging material prepared by the preparation method according to any one of claims 8 to 9 in water plugging of oil reservoirs.
Citation Information
Patent Citations
Polymer microsphere water shutoff profile control agent and preparation method thereof
CN111234792A
Epoxy resin authigenic particle profile adjusting system and application thereof
CN113025293A